MODEL PENGUATAN MATERI FIKIH DENGAN KONSEP SYARAT KECAKAPAN IBADAH AMALIAH (SKIA) DI MI AL AZHAR SENDURO LUMAJANG - Mahmuda, Imaniar; Hafid (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2026)
This research is based on the need to improve students' understanding and skills in performing worship in accordance with Islamic jurisprudence (fiqh) guidance in a practical and applicable way. This study aims to examine a model for reinforcing Islamic jurisprudence material based on the concept of the requirements for practical worship skills (SKIA) and to assess its effectiveness in improving students' overall ability to practice worship. The research method used was a descriptive qualitative approach. Data collection techniques were conducted through observation, interviews, and documentation. The results indicate that the application of the SKIA model can improve students' conceptual understanding and practical skills in worship, such as ablution, prayer, an d fasting. This model emphasizes the integration of understanding of Islamic jurisprudence theory and the practice of worship, taking into account the requirements of students' age, mental ability, and knowledge. Thus, the SKIA model has proven effective in strengthening Islamic jurisprudence learning in a more contextual way and oriented towards developing students' religious competence.. Keywords: Fiqh, Material Reinforcement, Model SKIA.